TRANSFORMATION OF LIFE AND PERSONAL VALUES SYSTEM OF MODERN UKRAINIAN YOUTH - Kruty, Kateryna; Rodiuk, Nataliia; Desnova, Iryna; Blashkova, Olena; Pakhalchuk, Natalia; Holiuk, Oksana; Stulika, Olena (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
The realities of modern Ukrainian's life at this historical moment of the struggle for independence in the conditions of social tension are quite complex and uncertain. Ukrainians are losing not only their material wealth, but life and personal values are changing in their minds. Everything that was important a year or two ago is not a priority now. The change of values, the search for a new meaning of life is one of the main fundamental principles of the modern Ukrainians' life. The main social task for every citizen is social and personal self-determination, as well as the active formation of a new worldview. Each individual is capable of realizing the value of his own life, as well as the lives of the people around him, based on his own worldview and his place in society. The formation of a person's ideas about values and value orientations presupposes their understanding and filling with specific content. The formation of values among modern Ukrainian youth occurs due to their connection with the outside world, the variety of social relations in which they are, and due to the knowledge of their own experiences. The main research methods: observation, survey, statistical analysis. The article emphasizes the identification of changes in personal values and value orientations of the youth of Ukraine. The main results of the research give reasons for asserting that the phenomenon of searching for life and personal values by a young person is one of the priority areas of scientific research. Due to the search, determination of the main and reshaping of the established value orientations of the modern youth of Ukraine, the worldview and meaning of life are changing. It is safe to say that such changes will help build own life path as a holistic process, as well as make one's abilities and opportunities of the environment as much as possible in solving life problems and achieving important goals. The author's interpretation of the terms "life values", "personal values", "value orientations of Ukrainian youth" is proposed.